BNA رقمنة القطاع المصرفي في الجزائر تجربة البنك الوطني الجزائري - العيد، حورية (University Of Eloued جامعة الوادي, 2024)
إن التطورات السريعة في التكنولوجيا الرقمية أصبحت ضرورية في العديد من المجالات، ولا يمكن الاستغناء عنها في قطاعات متعددة، وخصوصاً في القطاع المالي والمصرفي ، هذه التكنولوجيا تساهم في تسريع العمليات اليومية والمعاملات المالية والمصرفية، و التي قد أثبتت أهميتها في ظل هذه التغييرات، حيث أضحت قنوات مثل المواقع الإلكترونية، الإنترنت، البريد الإلكتروني، وأجهزة الصراف الآلي من الوسائل الأساسية التي يعتمد عليها العملاء في إجراء معاملاتهم. هذا التطور التكنولوجي خلق بيئة تنافسية حادة في القطاع المصرفي، مما زاد من ضرورة مواكبة البنوك المحلية لتوقعات العملاء وتحسين مستوى الخدمات التي تقدمها .. يهدف هذا البحث إلى إظهار أثر رقمنة القطاع المصرفي في تسهيل تقديم الخدمات المالية وتحسين أداء المؤسسات المالية، حيث أصبح من الضروري على القطاع المصرفي والمالي تجاوز الأساليب التقليدية والعمل على تحسين كفاءة الخدمات المصرفية باستخدام التكنولوجيا الحديثة و مثال على ذلك تجربة البنك الوطني الجزائري Abstract : The rapid advancements in digital technology have become essential in many fields and indispensable in various sectors, especially in the financial and banking sectors. This technology contributes to speeding up daily operations and financial and banking transactions, proving its importance amidst these changes. Channels such as websites, the internet, email, and ATMs have become fundamental means that customers rely on to carry out their transactions. This technological development has created a highly competitive environment in the banking sector, increasing the need for local banks to meet customer expectations and improve the quality of services they provide. This research aims to demonstrate the impact of the digitization of the banking sector in facilitating the provision of financial services and improving the performance of financial institutions. It has become necessary for the banking and financial sectors to move beyond traditional methods and work on enhancing the efficiency of banking services using modern technology, as exemplified by the experience of the National Bank of Algeria
Digitization of the Banking Sector in Algeria: The Experience of the National Bank of Algeria "
مداخلة
Keywords: القطاع المصرفي; الخدمات المالية; الخدمات المصرفية الجزائرية; الرقمنة; Banking sector; financial services; Algerian banking services; digitization